EXPERIMENTAL WORK ON THE USE OF PEDAGOGICAL VIEWS OF KHOREZM JADIDS - Ibodullayeva Zubayda Sherzodovna; Rakhmonov Oybek (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
The introduction of the essay Experimental Work on the Use of Pedagogical Views of Khorezm Jadids sets the stage for an exploration of the profound educational reforms advocated by the Jadids, a reformist movement that emerged in the late 19th and early 20th centuries in Turkestan.